FERTILIZATION RESPONSE AND NITROGEN NUTRITION DIAGNOSIS OF A NATURAL GRASSLAND IN SOUTHERN BRAZIL - Viégas, Julio; Bittencourt de Oliveira, Leandro; Brum de Souza, Iraline; Cruz, Pablo; Ferreira de Quadros, Fernando Luiz; Tiecher, Tales (Acta Iguazu, 2017)
Natural grasslands found in Campos Biome in Southern Brazil are the main forage source for production approximately 13 million cattle and 5 million sheep. The forage yield is often limited by the soil fertility, which is naturally low. This study aimed to test the response of natural grassland to fertilization and to assess the level of N nutrition index (NNI) achieved with fertilization by using a dilution curve model. The experimental design was a factorial arrangement in sub-divided plots, where the landscape was considered the main plot and fertilization the subplots, with three replicates. In the fertilized treatment were applied 310 kg ha–1 of N, 160 kg ha–1 of P2O5, 160 kg ha–1 of K2O, and 3 Mg ha–1 of dolomitic lime. No fertilization was applied in the non-fertilized treatment (natural soil fertility). Herbage mass was evaluated over 224 days of growth by harvesting all the aboveground plant biomass in a 0.25 m2 quadrat. Herbage mass was higher in the fertilized treatment from 180 to 224 days of growth. At 180 days of growth, herbage mass was 7.8 Mg ha–1 in the fertilized treatment and 3.0 Mg ha–1 in the non-fertilized treatment. Generally, herbage mass accumulation from 83 to 180 days of growth was 3.2 times as high in the fertilized (62 kg ha–1 day–1) than in the non-fertilized treatment (20 kg ha–1 day–1). The N dilution curve model was successfully tested under high and low soil fertility conditions. At 83, 109, and 136 days of growth in the fertilized treatment, the nitrogen nutrition index (NNI) was 95, 103 and 92, respectively; while in the non-fertilized treatment, the NNI was always lower than 52. Therefore, the level of nitrogen nutrition index (NNI) estimated by the N dilution curve model was a good indicator of N availability to the natural grassland, and can be used for assessing the N nutrition status during the growth of natural grassland in Southern Brazil.